Boricua Founder Variant in FRRS1L Causes Epileptic Encephalopathy With Hyperkinetic Movements. (February 2021) - Abdelmoumen, Imane; Jimenez, Sandra; Valencia, Ignacio; Melvin, Joseph; Legido, Agustin; Diaz-Diaz, Mayela M.; Griffith, Christopher; Massingham, Lauren J.; Yelton, Melissa; Rodríguez-Hernández, Janice; Schnur, Rhonda E.; Walsh, Laurence E.; et al.
Objective: To describe a founder mutation effect and the clinical phenotype of homozygous FRRS1L c.737_739delGAG (p.Gly246del) variant in 15 children of Puerto Rican (Boricua) ancestry presenting with early infantile epileptic encephalopathy (EIEE-37) with prominent movement disorder. Background: EIEE-37 is caused by biallelic loss of function variants in the FRRS1L gene, which is critical for AMPA-receptor function, resulting in intractable epilepsy and dyskinesia. Methods: A retrospective, multicenter chart review of patients sharing the same homozygous FRRS1L (p.Gly246del) pathogenic variant identified by clinical genetic testing. Clinical information was collected regarding neurodevelopmental outcomes, neuroimaging, electrographic features and clinical response to antiseizure medications. Results: Fifteen patients from 12 different families of Puerto Rican ancestry were homozygous for the FRRS1L (p.Gly246del) pathogenic variant, with ages ranging from 1 to 25 years. The onset of seizures was from 6 to 24 months. All had hypotonia, severe global developmental delay, and most had hyperkinetic involuntary movements. Developmental regression during the first year of life was common (86%). Electroencephalogram showed hypsarrhythmia in 66% (10/15), with many older children evolving into Lennox-Gastaut syndrome. Six patients demonstrated progressive volume loss and/or cerebellar atrophy on brain magnetic resonance imaging (MRI). Conclusions: We describe the largest cohort to date of patients with epileptic encephalopathy. We estimate that 0.76% of unaffected individuals of Puerto Rican ancestry carry this pathogenic variant due to a founder effect. Children homozygous for the FRRS1L (p.Gly246del) Boricua variant exhibit a very homogenous phenotype of early developmental regression and epilepsy, starting with infantile spasms and evolving into Lennox-Gastaut syndrome with hyperkinetic movement disorder.